An Efficient and Environmental Benign Synthesis of 2-benzimidazoles and 2-benzothiazoles Using CeCl3-NaI as Catalyst. (February 2013) - Zhu, Xun; Wei, Yunyang
A one-pot condensation of an aldehyde with 1, 2-phenylenediamine or 2-aminothiophenol in dimethyl carbonate at 100 °C under O2 in the presence of catalytic amounts of CeCl3 –NaI gave an imine intermediate, which cyclised and dehydrogenated to give 2-arylbenzimidazoles or 2-arylbenzothiazoles in good yields.